Fine tuning of ferromagnet/antiferromagnet interface magnetic anisotropy for field-free switching of antiferromagnetic spins. Issue 35 (28th August 2020) - Ślęzak, M.; Dróżdż, P.; Janus, W.; Nayyef, H.; Kozioł-Rachwał, A.; Szpytma, M.; Zając, M.; Menteş, T. O.; Genuzio, F.; Locatelli, A.; Ślęzak, T.
Abstract : We show that in a uniform thickness NiO(111)/Fe(110) epitaxial bilayer system, at given temperature near 300 K, two magnetic states with orthogonal spin orientations can be stabilized in antiferromagnetic NiO. Abstract : We show that in a uniform thickness NiO(111)/Fe(110) epitaxial bilayer system, at given temperature near 300 K, two magnetic states with orthogonal spin orientations can be stabilized in antiferromagnetic NiO. Field-free, reversible switching between these two antiferromagnetic states is demonstrated. The observed phenomena arise from the unique combination of precisely tuned interface magnetic anisotropy, thermal hysteresis of spin reorientation transition and interfacial ferromagnet/antiferromagnet exchange coupling. The possibility of field-free switching between two magnetic states in an antiferromagnet is fundamentally interesting and can lead to new ideas in heat assisted magnetic recording technology.